Pengaruh Metode Demonstrasi Terhadap Hasil Belajar Siswa pada Materi Sistem Pencernaan Kelas XI IPA SMA - Vera Roring; Anita Amelia Ole (Departement of Mathematics Education, 2022)
This research aims to determine the effect of the demonstration method on student learning outcomes in the digestive system material for class XI high school science. The independent variable in this research is the demonstration method while the dependent variable is the learning outcomes. This research was carried out at SMA Negeri 1 Ratahan with a population of all SMA N 1 Ratahan students. The sample for this research was class XI IPA2 as the experimental class and XI IPA1 as the control class. The null hypothesis (H0) in this research is that there is no influence of the demonstration method on learning outcomes, while the working hypothesis (H1) in this research is that there is an influence of the demonstration method on learning outcomes. This research succeeded in showing that there was a significant influence of the demonstration method on student learning outcomes in the digestive system material in the experimental class, whereas in the control class, there was no significant influence. Based on the t-test analysis with a significance level of 0.05, t-count was obtained with a value of 13.7 and table with a value of 2.10, t-count > t-table.